CLINICAL MANIFESTATION, DIAGNOSTICS AND TREATMENT OF KAWASAKI DISEASE: KNOWN DATA AND UNSOLVED QUESTIONS - G. А. Lyskina; O. G. Shirinskaya (Вопросы современной педиатрии)
The lecture deals with the most common systemic vasculitis in pediatric practice — Kawasaki disease. This disorder is associated with risk of myocardial infarction and sudden cardiac death in children and young adults and at present is considered to be the main cause of the acquired heard diseases in children. The authors give historical aspects and modern opinions on etiology, pathogenesis, clinical manifestation, diagnostics and treatment of Kawasaki disease. The data were summarized from Russian and foreign literature as well as from the own authors’ experience.